Research on dimension coupling of piezoelectric three-component force unit based on sensor assembly error - Jun Zhang (Advances in Mechanical Engineering, 2019)
In the process of manufacturing and operation of mechanical equipment, accurate measurement of vector force provides an important basis for real-time control of working conditions and process adjustment to ensure the performance. Piezoelectric three-component force unit can be used to measure three-axis force with the characteristics of high frequency and stiffness, great dynamic response, and resistance to harsh conditions. Piezoelectric dynamometer consisting of four three-component force units can measure six-axis force/torque, which is widely used in vector force measurement. However, because of the limitation of manufacturing capability and assembly process, dimension coupling caused by assembly error of three-component force unit restricts improvement of test accuracy for itself and piezoelectric dynamometer. To reduce dimension coupling caused by displacement and angle assembly error, this article establishes a theoretical model of assembly error of three-component force unit. To achieve that the dimension coupling of three-component force unit is less than 3%, stiffness of relevant components is obtained by simulation analysis and experiment, and assembly tolerance range of three-component force unit is proposed. Four three-component force units are assembled to meet assembly tolerance range, and the calibration experiment is performed. The results show that the maximum of dimension coupling is less than 2.5%, which verifies the rationality of assembly tolerance range and further proves the reliability of the theoretical model. The theoretical model of assembly error clarifies the assembly accuracy of three-component force unit to ensure its test accuracy, which can further improve test accuracy of dynamometer. This article will also provide theoretical reference basis for this kind of sensors.